Clinicopathologic Analysis of Primary Adrenal Diffuse Large B-Cell Lymphoma: A Reappraisal of 23 Japanese Patients Based on EBV Association and PD-L1 Expression in Tumor Cells. (December 2021) - Kawano, Tasuku; Tsuyuki, Yuta; Suzuki, Yuka; Shimada, Kazuyuki; Kato, Seiichi; Takahara, Taishi; Mori, Mayuko; Nakaguro, Masato; Sakakibara, Ayako; Nakamura, Shigeo; Satou, Akira
Abstract : Primary adrenal diffuse large B-cell lymphoma (PA-DLBCL) is rare. We investigate 23 Japanese patients with PA-DLBCL to understand the clinicopathologic features and biological behavior of this disease. The 17 males and 6 females had a median age of 74 years (range: 40 to 86 y). Tumor cells harbored Epstein-Barr virus–encoded small RNA (EBER) in 9 (39%) samples, including samples from the 2 patients with methotrexate-associated B-cell lymphoproliferative disorder. Programmed cell death ligand 1 (PD-L1) expression was detected in tumor cells of 6 (26%) samples, including 1 EBER + and 5 EBER − samples. Four (17%) patients exhibited an intravascular proliferating pattern, and all 4 patient samples showed positive staining for PD-L1 in tumor cells. Among those patients, 3 showed intravascular proliferating pattern accompanied by a diffuse extravascular proliferation of tumor cells, and 1 patient was diagnosed with intravascular large B-cell lymphoma. We divided the 23 patients into 3 groups: EBER + (n=9, 39%), EBER − PD-L1 + (n=5, 22%), and EBER − PD-L1 − (n=9, 39%). A comparison of the outcomes among the 3 groups showed significant differences in overall survival ( P =0.034). The EBER + group had the worst prognosis, and the EBER − PD-L1 − group had the best prognosis. We also compared the outcomes among the 3 groups that received rituximab-containing chemotherapies. Both the overall survival and progression-free survival were significantly different among these groups ( P <0.001 and P =0.002, respectively). In conclusion, we evaluated 3 types of PA-DLBCL and found that each had unique clinical, pathologic, and prognostic features. Our results suggested that immune senescence, iatrogenic immunodeficiency, and immune evasion contribute to the development of PA-DLBCL. Abstract : Supplemental Digital Content is available in the text.